Community Projects A Draft Handbook - Planning Commission (Planning Commission, 1952)
The under-current of life in its essence is the same throughout India. But the external manifestations differ over wide ranges from people to people, village to village, district to district, state to state and border to border. It will, therefore, be fantastic even to attempt a rigid pattern for the community projects that can apply, in minute details, to all the people. Much more so is it in the case of procedures for implementation. “The Community Projects,—A Draft Outline” was only an attempt to give a silhouette of the project as it could be visualised, based on our existing knowledge. the hope was that it would be used only as an outline and a point of reference, and that variations would be made, depending on local conditions in each individual project area, based chiefly on the enlightened wishes of the people. the present compilation is likewise being presented in a draft form. It is an enlargement of the Draft Outline and is intended to serve as a point of reference, for all workers engaged in community projects to indicate what the Community Project involves and how to make a beginning in the matter of implementation. The compilation is the product of the pooled efforts of experts in various fields in the Government of India, in the Technical Cooperation Administration, in the Ford Foundation Organization and also in other non-official agencies. As in the case of the Draft Outline, the present compilation is also expected to undergo a revision when experiences, have been gathered concerning the community projects, during the period of implementation, the present effort constituting only an interim thinking on the subject.
Community Projects A Draft Handbook
Government of India